Evaluation of Children for Epilepsy Surgery - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
To assess the possibility of streamlining the decision process for epilepsy surgery in children with intractable epilepsy, the value of MRI, video EEG, and SPECT was investigated retrospectively in a study of 353 patients at the Lingfield Epilepsy Centre, Great Ormond Street Hospital, and Institute of Child Health, London, UK).